Computation of ground reaction forces in ski jumping imitation jumps based on inverse dynamics - Fritz, J.; Kröll, J.; Lindorfer, J.; Schwameder, H. (Science and Skiing VII, 2018)
Performance diagnostics in ski jumping can be conducted on all levels of the research pyramid presented by Schwameder (2012). Tests on the lower two levels of this pyramid (singular physical components and singular coordination components) mainly focus on physical and motor prerequisites, which are particularly important for a successful take-off, whereas tests on the upper two levels of the pyramid (hill jumps under training and competition conditions) mainly focus on the movement skills themselves. The imitation jumps (mimicking exercises) on the third level combine these two aspects of physical and motor prerequisites and actual movement skills.